Berberine protects against lung injury induced by liver transplantation through upregulating PPARγ and suppressing NF-κB-mediated pyroptosis pathway - Wenna Liu; Xiaohui Liang; Mingxia Huo; Yongwang Wang; Guanghua Zhang (Acta Cirúrgica Brasileira)
ABSTRACT Purpose: We builted a orthotopic autologous liver transplantation (OALT) model in rats to evaluate the possible mechanisms of berberine against lung injury. Methods: Forty clean grade Sprague-Dawley rats (male, healthy, 250–280 g) were divided into five groups (n = 8): sham-operated group (group S), orthotopic autologous liver transplantation group (group T), berberine group (group B), peroxisome proliferator-activated receptor gamma (PPARγ) inhibitor GW9662 group (group G), and berberine + GW9662 group (group B+G). In group S, the relevant tissues around the liver were dissociated only. Orthotopic autologous liver transplantation was used in other groups, berberine 200 mg/kg/day was given one week before surgery in group B and group B+G. GW9662 1 mg/kg was intraperitoneally injected in group G and group B+G 4 hours before surgery. Blood samples were obtained for detecting PaO2 and the concentration of serum clam cell protein (CC16), surfactant protein-D (SP-D), interleukin (IL)-1β and IL-18. The immunohistochemical method detects the expression of PPARγ and nuclear factor-kappa B (NF-κB) in lung tissues. The expression of PPARγ, NF-κBand pyroptosis-related proteins were analysed by western blotting. Results: Rats exhibited increased histological lung injury following OALT. Liver transplantation caused upregulated CC16, SP-D, IL-18 and IL-1β levels, reduced PaO2 and the PPARγ expression, upregulated the NF-κB and pyroptosis-related protein expressions. BBR pretreatment greatly alleviates these lung damages induced by OALT. However, administration of GW9662 partially reversed the beneficial effects of BBR on lung injury. Conclusion: Berberine may play protective capacities against lung injury by upregulating PPARγ to downregulate the NF-κB-mediated pyroptosis pathway.